Formal genus of the value of justice in Indonesia - Sidik Sunaryo (Faculty of Law, University of Muhammadiyah Malang, 2021)
This research aimed to find the formal genus of the value of justice in Indonesia. As known, justice that holds the sense of plurality universally transcends the boundary of formality of narrative texts in a normative way. The plurality of the value of justice that is laden with universality transforms to the genus of the school of thoughts vis-à-vis justice throughout history. Reduced meaning of justice in the perspective and the process of legislation is not powerful enough to negate the genus of justice that inherently represents the fundamental characteristics of justice. The look of the legislative process attractively reflects the genus of hunger for power intended to justify ambitions among factions in the domain of democracy. The formality in the legislation no longer represents the principle of the definition of the legislation and it is getting further away from the reach of the definition of aspiration, let alone to become an inspiration of the objectives of the state as mandated in the constitution. Holistic approach used in this research to find out the formal genus of justice in Indonesia. This research found that religious matters in the legislation-related authorities have become an acceptable ornament among the piles of the works of morality. The integrity that has become the genus of justice morality has transformed into a collection of texts hanging all over the wall of the national parliament. Religions are used as tools of negotiation in the formulation and the making of narrative texts before they are further transformed into legislation. Religions and powers in legislation are competing to find their point of the genus of normativization as expected by each faction. Law came into existence earlier than expected, leaving behind its umbilical cord like a prematurely born soul, the cord through which the values of justice are transferred from its mother, and these values have the dimension of plurality. Law is born, but since it is separable from its genus, it does not carry much of the meaning of birth.